Sixth young geotechnical engineers symposium 12th-14th April 2000 (Thomas Telford, 2000)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of conference held at City University, 12-14 April 2000.